การผลิตอนุภาคนาโนแคลเซียมคาร์บอเนตจากเปลือกหอยแมลงภู่ - อรนุช บุญสมปอง (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This study was the synthesis of calcium carbonate nanoparticles from mussel shells. The processing making shell waste economically valuable and zero waste technology. The factors affecting the formation of calcium carbonate to propose the easiest and most energy-efficient to produce calcium carbonate nanoparticles from mussel shells. The appropriate concentration of the variable solution is 4 molar potassium hydroxide (KOH) solution and 20% hydrogen peroxide (H2O2) solution, the grinding force to makes the calcium carbonate powder is the key parameter that makes nano-sized of calcium carbonate. The spectra from attenuated total reflectance Fourier transform infrared spectroscopy that shown in the transmittance range 1427, 1083 and 851 cm-1 which indicated the character of aragonite. The morphology from scanning electron microscopy was exhibited that calcium carbonate particles were nano-sized and observed in a cubic shape.